Perceived happiness as a tool to tackle mental health issues among pre-university students - Mamat, Asniza; Abdul Razak, Mohd Sufie; Zubir, Nazira; Mohd Shaharuddin, Norfazlina; Md Nor, Nurur Raudzah; Sidek, Muhammad Izzuddin (CENTRE FOR FOUNDATION STUDIES, INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA, 2024)
Understanding perceived happiness helps researchers and professionals design interventions and policies that can positively impact individuals' subjective well-being and contribute to improved mental health outcomes. The perceived happiness among CFS IIUM students is investigated. The outcome from the study serves as a vital platform in proposing an intervention initiative aimed at addressing mental health issues within this demographic. The mental well-being of tertiary students is of paramount concern due to the unique challenges associated with academic pressures, social transitions, and personal development during this critical phase of life. The study employs qualitative insights derived from interviews and focus group discussions. In response to the findings, the proposed intervention initiative is designed to be multifaceted. It integrates mental health awareness campaigns, skill-building workshops for stress management, and the establishment of support networks within the university community. The initiative also incorporates technological solutions, such as mobile applications for mental health tracking and access to resources. The effectiveness of the intervention is assessed through pre- and post-intervention surveys, tracking changes in perceived happiness and stress levels over the course of the initiative. Qualitative data further enriches the evaluation by capturing the nuanced experiences and perceptions of participating students.